Negative and positive urgency as pathways in the intergenerational transmission of suicide risk in childhood - Ortin-Peralta, Ana; Schiffman, Amara; Malik, Jill; Polanco-Roman, Lillian; Hennefield, Laura; Luking, Katherine (Frontiers in Psychiatry, 2024)
Introduction Parental suicide attempts and suicide death increase suicide risk in their offspring. High levels of impulsivity have been observed in families at high risk for suicide. Impulsivity, a highly heritable trait that is especially elevated in childhood, is frequently measured with the UPPS-P Impulsive Behavior Scale, which includes negative urgency, positive urgency, sensation seeking, premeditation, and perseverance. Our study examined the association between the UPPS-P facets and suicide ideation (without suicide attempts) and suicide attempts at baseline and first-time endorsement within the next two years in childhood. We also examined how the UPPS-P facets mediated the association between parental suicide attempts and suicide death and offspring first-time suicide ideation and attempts at follow-up. Methods The sample was 9,194 children (48.4% female; 9-10 years old) from the Adolescent Brain Cognitive Development (ABCD) study, assessed yearly three times. At Time 1 (T1), caregivers reported on suicide attempts and suicide deaths (combined) of the biological parents. Caregivers and children reported on suicide ideation and attempts in the KSADS-PL DSM-5 at each time point, T1 and follow-up (T2 and/or T3). The Short UPPS-P Scale (child-report) assessed the impulsivity facets at T1, which were computed as latent variables. Results At T1, 6.7% of children had a parent who had attempted or died by suicide. Most UPPS-P facets were associated with suicide ideation and attempts at T1 and T2/T3. In adjusted models, parental suicide attempts and suicide death were associated with offspring negative and positive urgency. In mediation models, parental suicide attempts and suicide death had an indirect effect on offspring first-time suicide ideation at T2/T3 through negative urgency (OR = 1.04; 95% CI, 1.01-1.08) and positive urgency (OR = 1.03, 95% CI, 1.01-1.05). Similar results were found for first-time suicide attempts at T2/T3. Discussion Our findings support an impulsive pathway in the familial transmission of suicide risk. For all youth, interventions that target multiple UPPS-P facets may help prevent or reduce suicide risk. For offspring whose parents have attempted or died by suicide, clinicians should pay particular attention to children who impulsively act on extreme emotions, as they may be at higher suicide risk.